Vibrotactile sense and hand symptoms in blue collar workers in a manufacturing industry. - Flodmark, B T (1997)
OBJECTIVES: To study whether vibrotactile sense combined with questionnaires (subjective complaints) and a clinical examination (including scoring of the Stockholm workshop scale (sensorineural staging)) could serve as a screening procedure, in the health care service, for sensorineural symptoms. A group of blue collar workers exposed to vibration in a manufacturing industry (rock crushing plants) was used as the study group. Another group of workers not exposed to vibration but subjected to heavy manual work served as the control group. METHODS: Vibrotactile sense was determined. The index and the little fingers of both hands were investigated. A clinical examination was performed. Questionnaires were used for exposure data and for assessment of symptoms. RESULTS: Important findings were that impairment in vibrotactile sense correlated with impairment in grip force, cold sensitivity, and other sensorineural symptoms--such as numbness and tendency to drop items. Clinical findings such as Phalen's test and two point discrimination were related only in those workers with the poorest vibrotactile sense. There was a relation between vibrotactile sense and the Stockholm workshop scale (sensorineural staging) for the sensorineural symptoms. Muscle and joint problems were more often seen in workers with decreased vibrotactile sense. CONCLUSIONS: Tactilometry for assessment of vibrotactile sense is a useful tool in assessing and evaluating the severity of vibration induced neuromuscular symptoms and verifying the patients' clinical complaints. Heavy manual work without exposure to vibration may contribute to impairment of vibrotactile sense. The relation between impairment in vibrotactile sense and grip strength indicates that impaired sensory feedback may contribute to muscle weakness.